PRODUKTIVITAS PRIMER PERAIRAN PANTAI KAWASAN HUTAN MANGROVE DESA PAGATAN BESAR KECAMATAN TAKISUNG KABUPATEN TANAH LAUT PROPINSI KALIMANTAN SELATAN - Mijani Rahman (Fish Scientiae, 2019)
This study aims to determine the fertility of coastal areas and waters primary productivity of mangrove forest areas and their role in supporting aquatic ecosystems. The usefulness of this research is to get a picture of a body of water based on the indicators of fertility primary productivity of waters, and can be used as information for planning and management of aquatic natural resources, especially the mangrove areas. This study was conducted Pagatan Great Village, District Takisung, Tanah Laut. The sampling method in this research is purposive, ie a certain place that is considered important and can represent the state of the waters of the mangrove forest. The number of sampling stations as manyas three places. Station 1 represents the waters of the mangrove forest (phasa at hightide). Station 2 represent the muddy coastal waters (at the time of high tide and low tide),Station 3 represents the waters of the river mouth (during high tide and low tide). Eachstation is repeated 2 times. Based on the research results show the value of primary productivity in the waters of the mangrove forest ranged from 147.22 to 513.89 mg C /m3 / day of water and primary productivity coloum ranging from 133.330 to 506.245mg C / m3 / day. The fertility rate of the Pagatan village included in the fertility rate is Mesotrophic up to eutrophic waters with moderate to high levels of fertility.Phytoplankton abundance greater than zooplankton. The greatest abundance at Station 1(9820 cells / liter) and the lowest at station 2 (4240 cells / liter). The abundance of zooplankton found in station 1 (260 individuals / liter) and the lowest at station 3 (120 individuals / liter). This research is expected to be used as a location for monitoring and evaluation to determine the annual productivity of the waters of the mangrove forest ofthe village Pagatan.